Effects of Xiao Chengqi Formula on Slow Transit Constipation by Assessing Gut Microbiota and Metabolomics Analysis in vitro and in vivo - Zhou, Qian; Zhang, Di; Zhang, Heng; Wan, Xingyang; Hu, Bang; Zou, Qi; Su, Dan; Peng, Hui; Huang, Dandan; Ren, Donglin (Frontiers in Pharmacology, 2022)
The Xiao Chengqi (XCQ) formula is a newly constituted traditional Chinese medicine (TCM) prescription for the treatment of intestinal motility deficiency disease and is efficacious in those with slow transit constipation (STC). It is composed of Astragalus membranaceus, rhubarb, Salvia miltiorrhiza, Magnolia officinalis, Citrus aurantii, Angelica sinensis, Rehmannia glutinosa. To clarify the detailed mechanism by which XCQ formula promotes intestinal peristalsis, a rat model of STC was constructed and treated with the formula. Through 16S rDNA sequencing, metabolomics sequencing, and tissue RNA-seq, the effects of XCQ formula on intestinal microflora and metabolic level and the possible molecular mechanism of its regulation were explored. The results showed that the abundance of Roseburia spp. in the feces of STC rats decreased significantly and the content of butyl aminobenzene (BAB) in feces decreased significantly; the number of interstitial cells of Cajal (ICC) in the colon of STC rats also increased. Furthermore, in vitro and in vivo experiments suggested that BAB could activate IL-21R on ICC surface, up-regulate the phosphorylation expression of its downstream molecules STAT3 and ERK, and inhibit the apoptosis of ICC induced by loperamide. In conclusion, XCQ formula can protect ICC activity and effectively promote intestinal peristalsis by promoting the colonization of Roseburia and increasing the content of BAB after metabolism, thus improving the defecation status of STC patients.